Effect of ceftazidime/avibactam plus fosfomycin combination on 30 day mortality in patients with bloodstream infections caused by KPC-producing Klebsiella pneumoniae: results from a multicentre retrospective study. Issue 6 (7th December 2022) - Oliva, A; Volpicelli, L; Di Bari, S; Curtolo, A; Borrazzo, C; Cogliati Dezza, F; Cona, A; Agrenzano, S; Mularoni, A; Trancassini, M; Mengoni, F; Stefani, S; et al.
Abstract: Introduction: The primary outcome of the study was to evaluate the effect on 30 day mortality of the combination ceftazidime/avibactam + fosfomycin in the treatment of bloodstream infections (BSIs) caused by KPC-producing Klebsiella pneumoniae (KPC- Kp ). Materials and methods: From October 2018 to March 2021, a retrospective, two-centre study was performed on patients with KPC- Kp BSI hospitalized at Sapienza University (Rome) and ISMETT-IRCCS (Palermo) and treated with ceftazidime/avibactam-containing regimens. A matched cohort (1:1) analysis was performed. Cases were patients receiving ceftazidime/avibactam + fosfomycin and controls were patients receiving ceftazidime/avibactam alone or in combination with in vitro non-active drugs different from fosfomycin (ceftazidime/avibactam ± other). Patients were matched for age, Charlson comorbidity index, ward of isolation (ICU or non-ICU), source of infection and severity of BSI, expressed as INCREMENT carbapenemase-producing Enterobacteriaceae (CPE) score. Results: Overall, 221 patients were included in the study. Following the 1:1 match, 122 subjects were retrieved: 61 cases (ceftazidime/avibactam + fosfomycin) and 61 controls (ceftazidime/avibactam ± other). No difference in overall mortality emerged between cases and controls, whereas controls had more non-BSI KPC- Kp infections and a higher number of deaths attributable to secondary infections. Almost half of ceftazidime/avibactam + fosfomycin patients were prescribed fosfomycin without MIC fosfomycin availability. No difference in the outcome emerged after stratification for fosfomycin susceptibility availability and dosage. SARS-CoV-2 infection and ICS ≥ 8 independently predicted 30 day mortality, whereas an appropriate definitive therapy was protective. Conclusions: Our data show that fosfomycin was used in the treatment of KPC- Kp BSI independently from having its susceptibility testing available. Although no difference was found in 30 day overall mortality, ceftazidime/avibactam + fosfomycin was associated with a lower rate of subsequent KPC- Kp infections and secondary infections than other ceftazidime/avibactam-based regimens.